Diet in The Intensive Phase of Pulmonary Tuberculosis Patients - Desy Indra Yani; Hilman Saiful Islam; Citra Windani Mambang Sari (Journal of Nursing Care, 2018)
Diet is an important component in the treatment of tuberculosis (TB). The diet is a daily nutrition fulfillment. The nutrition means macronutrient and micronutrient. The lack of macronutrient and micronutrient intake in tuberculosis patients could be a high risk for patients. Lack of nutrition can be addressed from the low level of BMI in TB patients. Both malnutrition and TB influence each other, malnutrition increases the risk for TB and TB could cause malnutrition. The aim of this study was to describe the diet of tuberculosis patients in the intensive phase. The study was conducted in two primary health cares in Bandung city. This study was a descriptive-quantitative research that used consecutive sampling method. The samples were 36 TB patients in the intensive phase.  The data was gathered using 3 days food record and analyzed using the descriptive statistics method. The study’s result indicated that 86,1% of TB patients consumed calories less than their need, 80,6% of TB patients consumed carbohydrates meet the needs, 83,3% of TB patients consumed protein less than necessity,  55,6% of  TB patients consumed fat meet their needs, and 100% of TB patients consumed vitamin D less their need. The study results showed that the diet of TB patients was less than their need. This study concludes that in general, the diet in TB patients is still less than their need, especially protein and vitamin D. While carbohydrates and fat met the patients’need. Based on this result, the researcher recommends that the primary health care in Bandung city should provide counseling services about various food types that need to be consumed by TB patients to fulfill calory, protein, and vitamin D daily needs.